2011
DOI: 10.1111/j.1469-7610.2011.02432.x
|View full text |Cite
|
Sign up to set email alerts
|

Is sensory over‐responsivity distinguishable from childhood behavior problems? A phenotypic and genetic analysis

Abstract: Background Although impaired sensory processing accompanies various clinical conditions, the question of its status as an independent disorder remains open. Our goal was to delineate the comorbidity (or lack thereof) between childhood psychopathology and sensory over-responsivity (SOR) in middle childhood using phenotypic and behavior genetic analyses. Method Participants (N=970) were drawn from the Wisconsin Twin Project, a population-based sample of twins and their families. Mothers completed a sensory res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
51
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(56 citation statements)
references
References 33 publications
(43 reference statements)
4
51
0
1
Order By: Relevance
“…The absence of a high correlation between sensory and behavioral symptoms in both groups suggests that these symptoms reflect different conditions, which confirms our hypothesis and is supported by other studies [25,26,50]. It is important to note that the correlation between Withdrawn syndrome (on CBCL) and avoidance sensory symptoms (assessed with the ITSP) in children with RDSP was only moderate.…”
Section: The Relationship Between Sensory and Behavioral Symptomssupporting
confidence: 79%
See 1 more Smart Citation
“…The absence of a high correlation between sensory and behavioral symptoms in both groups suggests that these symptoms reflect different conditions, which confirms our hypothesis and is supported by other studies [25,26,50]. It is important to note that the correlation between Withdrawn syndrome (on CBCL) and avoidance sensory symptoms (assessed with the ITSP) in children with RDSP was only moderate.…”
Section: The Relationship Between Sensory and Behavioral Symptomssupporting
confidence: 79%
“…This question suggests that there is a need to analyze the relationship between these symptoms [17,[24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Many very young TD children express RRBs, including restricted interests, repetitive motor behaviors, change resistance, and/or atypical sensory responsiveness (Camarata 2014;Harrop et al 2013;Van Hulle et al 2012). In fact, Harrop et al (2013) noted that young TD children and young children diagnosed with ASD express similar rates of RRBs.…”
Section: Criteria Validity Research Approach 2: Do the Two Core Asd Dmentioning
confidence: 99%
“…However, this information is largely based on anecdotal case reports, 20,21 studies using a broader definition of sensory problems 14 (e.g., including both over- and under-responsiveness), and research using unsystematically diagnosed or poorly characterized samples. In the Carter et al 3 and Van Hulle et al 15 studies, rates of specific psychiatric disorders were not reported, but the rate of diagnoses within the broad domains of internalizing disorders among those with SOR ranged from 10.0% 3 to 70.4% 15 and externalizing disorders from 18.5% 3 to 50.4%. 15 …”
mentioning
confidence: 95%
“…Two large scale studies examined rates of SOR and co-occurring DSM-IV 13 diagnoses in well-characterized, population-based samples of typically developing children (i.e., children without cognitive disabilities or autism spectrum disorders). 3,14,15 Both samples were school-aged children (7–10 years old; 3 7 years old 15 ) whose parents completed a structured diagnostic interview (Diagnostic Interview Schedule for Children) 16 and the Sensory Over-Responsivity Inventory (SensOR), 17 a parent-report measure of SOR in the tactile and auditory domains. SOR status was based on the SensOR but criteria differed in each study, such that children were classified has having SOR if parents endorsed ≥ 4 items in the Carter et al study and ≥ 6 tactile or ≥ 4 auditory items in the Van Hulle et al study.…”
mentioning
confidence: 99%